Composite current collector and preparation method thereof, pole piece, battery and vehicle

By introducing a conductive resin layer and a conductive coating into the composite fluid collection, and using adhesives to enhance the interface binding force, the interface peeling problem in the existing composite fluid collection is solved, significantly improving the rate performance and fast charging capability of the battery.

CN119852419APending Publication Date: 2025-04-18CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410871356.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing graphene/organic thin film composite liquid collectors have interface peeling problems, resulting in reduced battery rate performance and increased resistivity.

Method used

A composite fluid including a conductive resin layer and a conductive coating is adopted. The conductive resin layer is composed of a polymer resin and a first conductive agent. The conductive coating is composed of a second conductive agent and a binder. The interface bonding strength is improved through the binder to avoid interface peeling.

Benefits of technology

The interface peel strength and current collection ability of the composite liquid collector are significantly improved, the interface impedance and resistivity are reduced, and the fast charging performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852419A_ABST
    Figure CN119852419A_ABST
Patent Text Reader

Abstract

The invention discloses a composite current collector and a preparation method thereof, a pole piece, a battery and a vehicle. The composite current collector comprises a conductive resin layer and a conductive coating, the conductive resin layer comprises polymer resin and a first conductive agent, the conductive coating is arranged on at least one side of the conductive resin layer, and the conductive coating comprises a second conductive agent and a binder. The composite current collector has relatively high interface peel strength, relatively strong current collection capability and relatively low interface impedance and resistivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a composite current collector and a preparation method thereof, a pole piece, a battery and a vehicle. Background Art

[0002] In the prior art, a graphene suspension is coated on an organic film, and after drying, it is rolled several times, and after being soaked in a mixed solution of acetone and isopropanol, it is rolled several times to obtain a graphene / organic film composite current collector. However, the current graphene / organic film composite current collector has the following problems: (1) The organic film layer in the middle is insulated, so that the current generated by the active materials on both sides of the electrode cannot be collected, and the battery impedance is increased, resulting in a decrease in the battery rate performance; (2) The interface bonding force between graphene and the organic film is weak, which easily causes interface peeling in an electrolyte environment or under charge and discharge conditions. Summary of the invention

[0003] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a composite current collector and a preparation method thereof, a pole piece, a battery and a vehicle. The composite current collector has high interface peeling strength, strong current collection ability and low interface impedance and resistivity.

[0004] In one aspect of the present invention, the present invention provides a composite current collector. According to an embodiment of the present invention, the composite current collector comprises:

[0005] A conductive resin layer, the conductive resin layer comprising a polymer resin and a first conductive agent;

[0006] A conductive coating is provided on at least one side of the conductive resin layer, and the conductive coating comprises a second conductive agent and a binder.

[0007] According to the composite current collector of the above embodiment of the present invention, it includes a conductive resin layer and a conductive coating, the conductive resin layer includes a polymer resin and a first conductive agent, the addition of the first conductive agent improves the current collection ability of the conductive resin layer, reduces the battery resistance, and improves the battery rate performance; the conductive coating is arranged on at least one side of the conductive resin layer, the conductive coating includes a second conductive agent and a binder, the binder in the conductive coating significantly improves the interface bonding strength between the conductive resin layer and the conductive coating, and avoids the interface peeling of the composite current collector in an electrolyte environment or under conditions such as charging and discharging. At the same time, due to the addition of the binder, the peeling strength between the composite current collector and the pole piece active material is improved, so that the composite current collector and the pole piece active material are in closer contact, and the interface impedance between the composite current collector and the pole piece active material is significantly reduced, thereby reducing the resistivity of the pole piece, and then improving the fast charging performance of the battery. As a result, the composite current collector has a high interface peeling strength, a strong current collection ability, and a low interface impedance and resistivity.

[0008] In addition, the composite current collector according to the above embodiment of the present invention may also have the following additional technical features:

[0009] In some embodiments of the present invention, the mass ratio of the polymer resin to the first conductive agent is (3:12) to (8:12). Thus, the current collecting capacity of the composite current collector can be improved.

[0010] In some embodiments of the present invention, the thickness of the conductive resin layer is 4 μm to 15 μm, thereby improving the current collection capacity of the composite current collector.

[0011] In some embodiments of the present invention, the polymer resin includes at least one of polyimide, polyethylene terephthalate and polypropylene.

[0012] In some embodiments of the present invention, the first conductive agent includes at least one of graphene, graphite, carbon black, acetylene black and carbon nanotubes.

[0013] In some embodiments of the present invention, the conductive resin layer further comprises a flame retardant, thereby improving the safety performance of the battery.

[0014] In some embodiments of the present invention, the flame retardant includes at least one of aluminum hydroxide, magnesium hydroxide and zinc borate.

[0015] In some embodiments of the present invention, based on the total mass of the conductive resin layer, the mass proportion of the flame retardant is 5 wt % to 30 wt %, thereby improving the safety performance of the battery.

[0016] In some embodiments of the present invention, the mass ratio of the second conductive agent to the binder is 1:(5-8). Thus, the interfacial peeling strength of the composite current collector can be improved and the resistivity of the composite current collector can be reduced.

[0017] In some embodiments of the present invention, the thickness of the conductive coating is 0.5 μm to 2 μm, thereby improving the interface peeling strength of the composite current collector and reducing the resistivity of the composite current collector.

[0018] In some embodiments of the present invention, the second conductive agent includes at least one of graphene, graphite, carbon black, acetylene black and carbon nanotubes.

[0019] In some embodiments of the present invention, the binder includes at least one of polyacrylic acid, styrene-butadiene rubber, polyamide and polyvinylidene fluoride.

[0020] In some embodiments of the present invention, the conductive coating further comprises a dispersant, thereby improving the dispersibility of the second conductive agent and the binder in the conductive coating.

[0021] In some embodiments of the present invention, the dispersant includes at least one of fatty alcohol polyoxyethylene ether, sodium carboxymethyl cellulose, maleic acid monopolyethylene glycol monomethyl ether ester, polyvinyl pyrrolidone, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

[0022] In some embodiments of the present invention, based on the total mass of the conductive coating, the mass proportion of the dispersant is 1 wt % to 3 wt %.

[0023] In a second aspect of the present invention, the present invention provides a method for preparing the composite current collector. According to an embodiment of the present invention, the method comprises:

[0024] (1) mixing and molding a material including a polymer resin and a first conductive agent to obtain a conductive resin layer;

[0025] (2) A conductive coating slurry including a second conductive agent and a binder is applied to at least one side of the conductive resin layer and then dried to obtain a composite current collector.

[0026] The materials including the polymer resin and the first conductive agent are mixed and molded to obtain a conductive resin layer. The addition of the first conductive agent improves the current collection ability of the conductive resin layer, reduces the battery resistance, and improves the battery rate performance. A conductive coating slurry including the second conductive agent and the binder is applied to at least one side of the conductive resin layer and then dried to obtain a composite current collector. The binder in the conductive coating significantly improves the interface bonding strength between the conductive resin layer and the conductive coating, and avoids the interface peeling of the composite current collector in an electrolyte environment or under conditions such as charging and discharging. At the same time, due to the addition of the binder, the peeling strength between the composite current collector and the pole piece active material is improved, so that the composite current collector and the pole piece active material are in closer contact, and the interface impedance between the composite current collector and the pole piece active material is significantly reduced, thereby reducing the resistivity of the pole piece, and then improving the fast charging performance of the battery. Therefore, the method can be used to prepare a composite current collector with high interface peeling strength, strong current collection ability, and low interface impedance and resistivity.

[0027] In addition, the method for preparing a composite current collector according to the above embodiment of the present invention may also have the following technical features:

[0028] In some embodiments of the present invention, in step (1), the mixed molding method includes compression molding, thereby improving the preparation efficiency of the conductive resin layer and saving time and cost.

[0029] In some embodiments of the present invention, the solid content of the conductive coating slurry is 10 wt % to 20 wt %.

[0030] In some embodiments of the present invention, the viscosity of the conductive coating slurry is 100 mPa·s to 500 mPa·s.

[0031] In a third aspect of the present invention, a pole piece is provided. According to an embodiment of the present invention, the pole piece includes the composite current collector or the composite current collector prepared by the method. Thus, the pole piece has lower resistance, higher conductivity and longer service life.

[0032] In a fourth aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery includes the above-mentioned pole piece. As a result, the battery has lower resistance, excellent fast charging performance and longer service life.

[0033] In a fifth aspect of the present invention, a vehicle is provided. According to an embodiment of the present invention, the vehicle comprises the above-mentioned battery. Thus, the vehicle has higher safety performance and longer service life.

[0034] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0036] Figure 1 is a schematic structural diagram of a composite current collector according to an embodiment of the present invention;

[0037] Figure 2 It is a schematic diagram of the process of preparing a composite current collector according to an embodiment of the present invention. DETAILED DESCRIPTION

[0038] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0039] The technical solution of the present invention is completed by the inventor based on the following findings: Compared with the currently used copper / aluminum foil metal current collector, the polymer resin is light in weight and can improve the energy density of the battery. At the same time, the polymer resin is not easily corroded by the electrolyte, which increases the service life of the current collector. Therefore, a graphene / organic film composite current collector is usually selected to replace the copper / aluminum foil metal current collector. However, the graphene / organic film composite current collector also has certain problems, such as the insulation of the organic film layer in the middle, which makes it impossible to collect the current generated by the active materials on both sides of the pole piece and increases the battery impedance; the interface bonding force between graphene and the organic film is weak, which is easy to cause interface peeling, directly affecting the service life of the composite current collector.

[0040] In view of this, in one aspect of the present invention, the present invention provides a composite current collector. According to an embodiment of the present invention, referring to Figure 1 The composite current collector includes: a conductive resin layer 100 and a conductive coating layer 200 .

[0041] According to an embodiment of the present invention, the conductive resin layer 100 includes a polymer resin and a first conductive agent. The addition of the first conductive agent improves the current collection capability of the conductive resin layer 100, reduces the battery resistance, and improves the rate performance of the battery. It should be noted that the polymer resin and the first conductive agent are conventional materials in the art, and those skilled in the art can select them according to actual conditions. For example, the polymer resin includes but is not limited to at least one of polyimide, polyethylene terephthalate, and polypropylene; the first conductive agent includes but is not limited to at least one of graphene, graphite, carbon black, acetylene black, and carbon nanotubes.

[0042] According to an embodiment of the present invention, the mass ratio of the polymer resin to the first conductive agent is (3:12) to (8:12). For example, the mass ratio of the polymer resin to the first conductive agent is 3:12, 4:12, 5:12, 6:12, 7:12, 8:12, etc. The inventors have found that by controlling the mass ratio of the polymer resin to the first conductive agent within the above range, the mechanical properties and the conductive properties of the conductive resin layer can be taken into account, so that the composite current collector has better active material carrying capacity and electronic conductivity.

[0043] According to an embodiment of the present invention, the thickness of the conductive resin layer 100 is 4 μm to 15 μm. For example, the thickness of the conductive resin layer 100 is 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc. The inventors have found that by controlling the thickness of the conductive resin layer 100 within the above range, the composite current collector can have the ability to carry active materials without occupying too much space and weight in the battery.

[0044] According to an embodiment of the present invention, the conductive resin layer 100 further includes a flame retardant. By adding the flame retardant to the conductive resin layer 100, thermal runaway of the battery can be prevented and battery safety can be improved. Further, the flame retardant includes but is not limited to at least one of aluminum hydroxide, magnesium hydroxide and zinc borate.

[0045] According to an embodiment of the present invention, the mass proportion of the flame retardant is 5wt% to 30wt% based on the total mass of the conductive resin layer 100. For example, the mass proportion of the flame retardant is 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, etc. The inventors have found that based on the total mass of the conductive resin layer 100, by controlling the mass proportion of the flame retardant within the above range, the impact on the mechanical properties and conductive properties can be reduced while ensuring the flame retardant ability of the composite current collector.

[0046] According to an embodiment of the present invention, the conductive coating 200 is provided on at least one side of the conductive resin layer 100, and the conductive coating 200 includes a second conductive agent and a binder. The binder in the conductive coating 200 significantly improves the interfacial bonding strength between the conductive resin layer 100 and the conductive coating 200, and avoids the interfacial peeling of the composite current collector in an electrolyte environment or under conditions such as charge and discharge. At the same time, due to the addition of the binder, the peeling strength between the composite current collector and the pole piece active material is improved, so that the composite current collector and the pole piece active material are in closer contact, and the interfacial impedance between the composite current collector and the pole piece active material is significantly reduced, thereby reducing the resistivity of the pole piece, thereby improving the fast charging performance of the battery. It should be noted that the second conductive agent is a conventional material in the art, and those skilled in the art can select it according to actual conditions. For example, the second conductive agent includes but is not limited to at least one of graphene, graphite, carbon black, acetylene black and carbon nanotubes.

[0047] According to an embodiment of the present invention, the binder includes at least one of polyacrylic acid, styrene-butadiene rubber, polyamide and polyvinylidene fluoride. The above binder can have good bonding ability to both polymer resin and conductive agent, significantly improve the interface bonding strength between the conductive resin layer and the conductive coating, avoid interface peeling of the composite current collector in an electrolyte environment or under charging and discharging conditions, ensure reliability during use, and have good stability in the battery system, and no side reactions will occur to affect battery performance.

[0048] According to an embodiment of the present invention, the mass ratio of the second conductive agent to the binder is 1:(5-8). For example, the mass ratio of the second conductive agent to the binder is 1:5, 1:6, 1:7, 1:8, etc. The inventors have found that by controlling the mass ratio of the second conductive agent to the binder within the above range, it is possible to ensure that the conductive coating has good conductivity and sufficient bonding strength with the conductive resin layer.

[0049] According to an embodiment of the present invention, the thickness of the conductive coating 200 is 0.5 μm to 2 μm. For example, the thickness of the conductive coating 200 is 0.5 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.8 μm, 2 μm, etc. The inventors have found that the thickness of the conductive coating 200 is controlled within the above range, which can improve the peel strength between the composite current collector and the pole sheet active material and reduce the resistivity of the pole sheet without occupying too much space and weight in the battery.

[0050] According to an embodiment of the present invention, the conductive coating 200 further includes a dispersant. By adding the dispersant to the conductive coating 200, the dispersion uniformity of the second conductive agent and the binder in the conductive coating 200 can be improved, thereby improving the electron transmission ability and bonding performance of the conductive coating 200. Further, the dispersant includes at least one of fatty alcohol polyoxyethylene ether, sodium carboxymethyl cellulose, maleic acid monopolyethylene glycol monomethyl ether ester, polyvinyl pyrrolidone, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

[0051] According to an embodiment of the present invention, based on the total mass of the conductive coating, the mass proportion of the dispersant is 1wt% to 3wt%. For example, the mass proportion of the dispersant is 1wt%, 1.5wt%, 2wt%, 2.5wt%, 2.8wt%, 3wt%, etc. The inventors have found that based on the total mass of the conductive coating, the mass proportion of the dispersant is controlled within the above range, which can play a good dispersing role on the conductive coating slurry.

[0052] In a second aspect of the present invention, the present invention provides a method for preparing the composite current collector. Figure 2 , the method comprising:

[0053] S100: Mixing and molding materials including a polymer resin and a first conductive agent

[0054] In this step, the material including the polymer resin and the first conductive agent is mixed and molded to obtain a conductive resin layer. The addition of the first conductive agent improves the current collection capacity of the conductive resin layer, reduces the battery resistance, and improves the rate performance of the battery. It should be noted that in order to obtain a conductive resin layer with excellent performance, the polymer resin and the first conductive agent are mixed as evenly as possible before the material including the polymer resin and the first conductive agent are mixed and molded.

[0055] According to an embodiment of the present invention, the hybrid molding method includes compression molding. The inventors have found that the compression molding preparation process can improve the preparation efficiency of the conductive resin layer and save time and cost while ensuring the performance of the conductive resin layer.

[0056] S200: applying a conductive coating slurry including a second conductive agent and a binder to at least one side of the conductive resin layer and then drying

[0057] In this step, a conductive coating slurry including a second conductive agent and a binder is applied to at least one side of the conductive resin layer and then dried to obtain a composite current collector. The binder in the conductive coating significantly improves the interfacial bonding strength between the conductive resin layer and the conductive coating, avoiding interfacial peeling of the composite current collector in an electrolyte environment or under charging and discharging conditions. At the same time, due to the addition of the binder, the peeling strength between the composite current collector and the pole piece active material is improved, making the composite current collector and the pole piece active material in closer contact, significantly reducing the interfacial impedance between the composite current collector and the pole piece active material, thereby reducing the resistivity of the pole piece, and further improving the fast charging performance of the battery.

[0058] According to an embodiment of the present invention, the solid content of the conductive coating slurry is 10wt% to 20wt%. For example, the solid content of the conductive coating slurry is 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, etc. The inventors have found that by controlling the solid content of the conductive coating slurry within the above range, the slurry can be guaranteed to have a suitable consistency, viscosity and uniformity, thereby ensuring the uniformity of the conductive coating and the stability during the coating process. Further, the solvent of the conductive coating slurry includes but is not limited to deionized water, ethanol, isopropyl ketone, N-methylpyrrolidone, N-dimethylformamide, etc.

[0059] According to an embodiment of the present invention, the viscosity of the conductive coating slurry is 100mPa·s to 500mPa·s. For example, the viscosity of the conductive coating slurry is 100mPa·s, 150mPa·s, 200mPa·s, 250mPa·s, 300mPa·s, 350mPa·s, 400mPa·s, 450mPa·s, 500mPa·s, etc. Controlling the viscosity of the conductive coating slurry within the above range can ensure that the slurry has suitable viscosity and rheology, thereby ensuring the uniformity of the conductive coating and the stability during the coating process.

[0060] It should be noted that the features and advantages described above for the composite current collector are also applicable to this method and will not be described in detail here.

[0061] In a third aspect of the present invention, a pole piece is provided. According to an embodiment of the present invention, the pole piece includes the composite current collector or the composite current collector prepared by the method. Thus, the pole piece has lower resistance, higher conductivity and longer service life.

[0062] According to an embodiment of the present invention, the electrode sheet is a positive electrode sheet, and the positive electrode sheet includes a composite current collector and a positive electrode active material layer, and the positive electrode active material layer is arranged on at least one side of the composite current collector.

[0063] According to an embodiment of the present invention, the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. It should be noted that the positive electrode active material, the conductive agent and the binder are conventional materials in the art, for example, the positive electrode active material includes but is not limited to lithium iron phosphate, lithium nickel oxide, lithium manganese oxide, lithium manganese phosphate, lithium manganese iron phosphate, etc.; the conductive agent includes but is not limited to conductive carbon black, carbon nanotubes, graphene, conductive graphite, etc.; the binder includes but is not limited to polyvinylidene fluoride, polytetrafluoroethylene and cellulose-based polymers.

[0064] According to an embodiment of the present invention, the electrode sheet is a negative electrode sheet, and the negative electrode sheet includes a composite current collector and a negative electrode active material layer, and the negative electrode active material layer is provided on at least one side of the composite current collector.

[0065] According to an embodiment of the present invention, the negative electrode active material layer includes a negative electrode active material, a conductive agent and a binder. It should be noted that the negative electrode active material, the conductive agent and the binder are conventional materials in the art, for example, the negative electrode active material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc.; the binder includes but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, cellulose-based polymers, etc.; the conductive agent includes but is not limited to conductive carbon black, carbon nanotubes, graphene, conductive graphite, etc.

[0066] It should be noted that the features and advantages described above for the composite current collector and its preparation method are also applicable to the pole piece and will not be described in detail here.

[0067] In a fourth aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery includes the above-mentioned pole piece. As a result, the battery has lower resistance, excellent fast charging performance and longer service life.

[0068] According to an embodiment of the present invention, the battery further comprises an electrolyte, and the electrolyte comprises an electrolyte salt and a solvent. The electrolyte salt and the solvent are conventional materials in the art, for example, the electrolyte salt includes but is not limited to lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate and lithium tetrafluorooxalate phosphate; the solvent includes but is not limited to ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, etc.

[0069] According to an embodiment of the present invention, the battery further includes a separator, which includes but is not limited to glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and the like.

[0070] It should be noted that the features and advantages described above for the electrode are also applicable to the battery and will not be repeated here.

[0071] In a fifth aspect of the present invention, the present invention provides a vehicle. According to an embodiment of the present invention, the vehicle includes the above-mentioned battery. As a result, the vehicle has higher safety performance and longer service life. For example, the vehicle may include but is not limited to a pure electric vehicle, a hybrid vehicle, etc.

[0072] It should be noted that the features and advantages described above for the battery are also applicable to the vehicle and will not be elaborated here.

[0073] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0074] Example 1

[0075] Polyimide, carbon black and graphite were uniformly dispersed in a mass ratio of 2:3:5 and then molded to prepare a 6μm thick conductive resin layer. Deionized water, dispersant (sodium carboxymethyl cellulose), binder (polyacrylic acid) and carbon black were added in a sand mill in a mass ratio of 61:1:51:7, and a conductive slurry with a solid content of 15wt% and a viscosity of 300mPa·s was obtained after sand milling for 3 hours. The conductive slurry was coated on both sides of the conductive resin layer and dried at 100℃ for 30s to obtain a composite current collector with a single-sided conductive coating thickness of 1μm.

[0076] Example 2

[0077] The difference between Example 2 and Example 1 is that the thickness of the conductive resin layer is 8 μm.

[0078] Example 3

[0079] The difference between Example 3 and Example 1 is that the thickness of the conductive resin layer is 15 μm.

[0080] Example 4

[0081] The difference between Example 4 and Example 1 is that in Example 4, polyethylene terephthalate is used instead of the polyimide in Example 1.

[0082] Example 5

[0083] The difference between Example 5 and Example 1 is that polyimide, carbon black and graphite are dispersed evenly in a ratio of 4:3:3 and then compression molded to prepare a 6 μm thick conductive resin layer.

[0084] Example 6

[0085] The difference between Example 6 and Example 1 is that the thickness of the single-sided conductive coating is 2 μm.

[0086] Example 7

[0087] The difference between Example 7 and Example 1 is that the thickness of the single-sided conductive coating is 0.5 μm.

[0088] Example 8

[0089] The difference between Example 8 and Example 1: Deionized water, dispersant (sodium carboxymethyl cellulose), binder (polyacrylic acid) and carbon black were added to a sand mill in a mass ratio of 61:1:35:7. After sand grinding for 3 hours, a conductive slurry with a solid content of 14 wt % and a viscosity of 230 mPa·s was obtained. The conductive slurry was coated on both sides of the conductive resin layer and dried at 100°C for 30 seconds to obtain a composite current collector with a conductive coating thickness of 1 μm on one side of the conductive resin layer.

[0090] Example 9

[0091] The difference between Example 9 and Example 1: Deionized water, dispersant (sodium carboxymethyl cellulose), binder (polyacrylic acid) and carbon black were added to a sand mill in a mass ratio of 61:1:56:7. After sand grinding for 3 hours, a conductive slurry with a solid content of 15wt% and a viscosity of 340mPa·s was obtained. The conductive slurry was coated on both sides of the conductive resin layer and dried at 100°C for 30s to obtain a composite current collector with a conductive coating thickness of 1μm on one side of the conductive resin layer.

[0092] Example 10

[0093] The difference between Example 10 and Example 1 is as follows: Deionized water, dispersant (sodium carboxymethyl cellulose), binder (polyacrylic acid) and carbon black are added to a sand mill in a mass ratio of 61:1:28:7. After sand milling for 3 hours, a conductive slurry with a solid content of 13wt% and a viscosity of 160mPa·s is obtained. The conductive slurry is applied on both sides of the conductive resin layer and dried at 100°C for 30s to obtain a composite current collector with a conductive coating thickness of 1μm on one side of the conductive resin layer.

[0094] Embodiment 11

[0095] The difference between Example 11 and Example 1: Deionized water, dispersant (sodium carboxymethyl cellulose), binder (polyacrylic acid) and carbon black were added to a sand mill in a mass ratio of 61:1:63:7. After sand grinding for 3 hours, a conductive slurry with a solid content of 15wt% and a viscosity of 400mPa·s was obtained. The slurry was coated on both sides of the conductive resin layer and dried at 100°C for 30s to obtain a composite current collector with a conductive coating thickness of 1μm on one side of the conductive resin layer.

[0096] Example 12

[0097] The difference between Example 12 and Example 1: Polyimide, carbon black, graphite, and flame retardant (aluminum hydroxide) are uniformly dispersed in a mass ratio of 2:3:5:1 and then compression molded to prepare a 6 μm thick conductive resin layer.

[0098] Comparative Example 1

[0099] The difference between Comparative Example 1 and Example 1 is that the polyimide is uniformly dispersed and then compression molded to prepare a 6 μm thick resin layer.

[0100] Comparative Example 2

[0101] The difference between Comparative Example 2 and Example 1: Deionized water, dispersant (sodium carboxymethyl cellulose) and carbon black were added to a sand mill in a mass ratio of 61:1:7. After sand grinding for 3 hours, a conductive slurry with a solid content of 12wt% and a viscosity of 60mPa·s was obtained. The conductive slurry was coated on both sides of the conductive resin layer and dried at 100°C for 30s to obtain a composite current collector with a conductive coating thickness of 1μm on one side of the conductive resin layer.

[0102] The properties of the composite current collectors prepared in Examples 1-12 and Comparative Examples 1-2 were measured in the following manner:

[0103] (1) Determination of the surface density of the composite current collector

[0104] Use 10000mm 2 Take 2 samples from 20mm on both sides of the same straight line in the width direction of the composite current collector sample, take 1 sample at the center, take 2 samples from the center at 200mm on both sides of the center, take 5 samples, and weigh each 10000mm in sequence with a balance (accuracy 0.1mg). 2 The mass m of the composite current collector is calculated as follows: The mass per unit area of ​​each composite current collector = m × 100 (g / m 2 ); then weigh the total mass M of the 5 samples and calculate: average composite current collector unit area mass = M / 5×100 (g / m 2 ). The surface density of the composite current collector affects the energy density of the battery. Compared with the currently used copper / aluminum foil metal current collector, the polymer resin composite current collector is light in weight and can improve the energy density of the battery.

[0105] (2) Determination of the mechanical properties of the composite current collector

[0106] Cut 5 longitudinal specimens with a width of 15mm from the composite current collector. The specimens are guaranteed to be smooth, free of burrs and obvious mechanical damage. The universal mechanical testing machine is calibrated and zeroed. The tensile speed is set to 50mm / min and the gauge length is 50mm. After the specimen is clamped, the displacement is reset to zero, the test is started, and 5 sets of tensile strength and elongation data are recorded. The strength and elongation of the composite current collector affect the yield of the pole piece during coating and rolling. Too low strength and elongation will cause the pole piece to break.

[0107] (3) Determination of resistivity of composite current collector

[0108] Use a sampler to cut a composite current collector disc with a diameter of 30mm, place it on the test platform of the four-probe tester, select the four-probe test mode as film resistivity, the test current is 500mA, and after the probe is lowered to make good contact with the composite current collector, click the "start test button" to record 3 sets of test results. The resistivity of the composite current collector affects the battery impedance and rate performance. The smaller the resistivity of the composite current collector, the better the electron transmission ability and the better the battery fast charging ability.

[0109] (4) Peel force test

[0110] The composite current collector was subjected to a peeling force test. The tape was pasted on the surface of the conductive coating to peel off the conductive coating from the conductive resin layer. The composite current collector was then cut into samples with a length of 100 mm and a width of 15 mm. The samples were fixed on a flat thin steel plate with double-sided tape. The free end of the composite current collector and the steel plate were clamped in the upper and lower clamps of the peeling force tester respectively. The samples were peeled off at an angle of 180° at a peeling speed of 50 mm / min. Three groups of test results were recorded and the average value was taken.

[0111] The performance test results of the composite current collectors prepared in Examples 1-12 and Comparative Examples 1-2 are shown in Table 1.

[0112] Table 1

[0113]

[0114] As shown in Table 1, the composite current collectors of Examples 1-12 have higher tensile strength and elongation, and the resistivity of the composite current collectors of Examples 1-12 is lower than that of Comparative Examples 1-2 and the peeling force is higher than that of Comparative Examples 1-2. At the same time, since the thickness of the conductive coating of Example 7 is less than that of Comparative Example 2, its surface density is lower than that of Comparative Example 2, and the binder ratio in Example 10 is reduced, resulting in its peeling strength being lower than that of Comparative Example 1; in addition, since the strength and elongation of the polyimide in the resin layer of Comparative Example 1 are higher, the mechanical properties are good but the conductivity is not there, the composite current collector of Comparative Example 1 has high strength and elongation, but high resistivity. This shows that the composite current collector composed of the present invention has high interface peeling strength, strong current collection ability, and low interface impedance and resistivity.

[0115] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0116] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A composite current collector, characterized in that: include: A conductive resin layer, the conductive resin layer comprising a polymer resin and a first conductive agent; A conductive coating is provided on at least one side of the conductive resin layer, and the conductive coating comprises a second conductive agent and a binder.

2. The composite current collector according to claim 1, characterized in that: The mass ratio of the polymer resin to the first conductive agent is (3:12) to (8:12).

3. The composite current collector according to claim 1 or 2, characterized in that: The thickness of the conductive resin layer is 4 μm to 15 μm.

4. The composite current collector according to claim 1 or 2, characterized in that: The polymer resin includes at least one of polyimide, polyethylene terephthalate and polypropylene; and / or The first conductive agent includes at least one of graphene, graphite, carbon black, acetylene black and carbon nanotubes.

5. The composite current collector according to claim 1 or 2, characterized in that: The conductive resin layer further includes a flame retardant; The flame retardant includes at least one of aluminum hydroxide, magnesium hydroxide and zinc borate.

6. The composite current collector according to claim 5, characterized in that: Based on the total mass of the conductive resin layer, the mass proportion of the flame retardant is 5 wt % to 30 wt %.

7. The composite current collector according to claim 1 or 2, characterized in that: The mass ratio of the second conductive agent to the binder is 1:(5-8).

8. The composite current collector according to claim 1 or 2, characterized in that: The thickness of the conductive coating is 0.5 μm to 2 μm.

9. The composite current collector according to claim 1 or 2, characterized in that: The second conductive agent includes at least one of graphene, graphite, carbon black, acetylene black and carbon nanotubes; and / or The binder includes at least one of polyacrylic acid, styrene-butadiene rubber, polyamide and polyvinylidene fluoride.

10. The composite current collector according to claim 1 or 2, characterized in that: The conductive coating further includes a dispersant; The dispersant includes at least one of fatty alcohol polyoxyethylene ether, sodium carboxymethyl cellulose, maleic acid monopolyethylene glycol monomethyl ether ester, polyvinyl pyrrolidone, sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

11. The composite current collector according to claim 10, characterized in that: Based on the total mass of the conductive coating, the mass proportion of the dispersant is 1 wt% to 3 wt%.

12. A method for preparing the composite current collector according to any one of claims 1 to 11, characterized in that: include: (1) mixing and molding a material including a polymer resin and a first conductive agent to obtain a conductive resin layer; (2) A conductive coating slurry including a second conductive agent and a binder is applied to at least one side of the conductive resin layer and then dried to obtain a composite current collector.

13. The method according to claim 12, characterized in that In step (1), the mixed molding method includes compression molding.

14. The method according to claim 12 or 13, characterized in that The solid content of the conductive coating slurry is 10 wt% to 20 wt%.

15. The method according to claim 12 or 13, characterized in that The viscosity of the conductive coating slurry is 100 mPa·s to 500 mPa·s.

16. A pole piece, characterized in that: The composite current collector comprises the composite current collector described in any one of claims 1 to 11 or prepared by the method described in any one of claims 12 to 15.

17. A battery, characterized in that: Including the pole piece as described in claim 16.

18. A vehicle, characterized in that: Comprising the battery of claim 17.